Digitization in the crisis: Gender, Concentration and Organizing. Perspectives for representatives of workers interests. - Schöggl, Astrid; Berger, Christian (Momentum Quarterly, 2022)
Digital technologies are based on mathematical models that follow a 1- or 0-logic. These models are not laws of nature, but the attempt to map reality in a codified way. Accordingly, technologies are not neutral. Instead, they represent existing power relations and can even promote their solidification. During the Corona crisis, a large part of both professional and private social life was shifted into the digital space. As a result, central areas of conflict in digitization that workers’ representatives deal with can be observed in sharp focus. This paper discusses the following: the gendered division of labor and the reversal of public vs. private, the concentration of power and capital among ICT corporations, and the crisis of organization in a digital world of work. Meeting these challenges requires representatives of workers interests to view technological change as a social process, to comprehend these power relations, and to find appropriate responses.